Improving Complex Problem-Solving in Emergency Response: A Study of the Fire and Rescue Service in Sweden - Lotta Vylund; Joel Jacobsson; Tove Frykmer; Kerstin Eriksson (International Journal of Disaster Risk Science)
Abstract This study explored how the Swedish Fire and Rescue Service identifies problems and implements necessary actions during complex problem-solving in emergencies, aiming to increase our understanding of this process. Primary and secondary data from large-scale fire events were analyzed, including semistructured interviews and incident reports. The concept of “possibility space” is applied to identify factors affecting complex problem-solving. This refers to the scope of action available at a specific point in time for a particular operation. The study identified eight factors, including problem identification, incident development, capability, collaboration, management, legal framework, logistics, and time available, that could either decrease or increase the scope of action. The findings contribute to an increased understanding of complex problem-solving in real-world environments and suggest that the possibility space could be a valuable tool for practitioners in enhancing problem-solving during emergency response.